2003
DOI: 10.1021/la026841w
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Nitrate Reductase Immobilized in Self-Assembled Structures with Redox Polyviologen

Abstract: We report on a novel bioelectrode based on self-assembled multilayers of nitrate reductase (NR) intercalated with a cationic viologen-functionalized polyvinylpyridinium (PV) polymer specially synthesized for this purpose. Different samples of polymer proved to have varying substitution ratios, according to NMR experiments. The electrostatic self-assemblies were built up on a thiol-modified gold surface using a strategy previously described by Hodak et al. The electrochemical behavior of PV and the response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…We found that k ET does not systematically depend on the nature of the film topmost layer or salt concentration and we note that the average k ET = (360 AE 130) s À1 is very close to the value k S = 250 s À1 for the same complex covalently tethered to a thiol layer with the same number of CH 2 groups as the MPS thiol. [55] On the other hand, for the complex Os(bpy) 3 2 + /3 + in solution, k 0 = (1.55 AE 0.03) 10 À2 cm s À1 , [64] which is much higher than the k 0 values in Table 1, but assuming D % 1-2 10 À6 cm 2 s À1 for the soluble species, one obtains k ET % 100-500 s…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…We found that k ET does not systematically depend on the nature of the film topmost layer or salt concentration and we note that the average k ET = (360 AE 130) s À1 is very close to the value k S = 250 s À1 for the same complex covalently tethered to a thiol layer with the same number of CH 2 groups as the MPS thiol. [55] On the other hand, for the complex Os(bpy) 3 2 + /3 + in solution, k 0 = (1.55 AE 0.03) 10 À2 cm s À1 , [64] which is much higher than the k 0 values in Table 1, but assuming D % 1-2 10 À6 cm 2 s À1 for the soluble species, one obtains k ET % 100-500 s…”
mentioning
confidence: 79%
“…[1] The method, based on the alternate adsorption of positively and negatively charged macro-molecules, enables an unprecedented control over film thickness, composition, and electrochemical behavior. Following the first examples of LbL-modified electrodes in 1997, the toolbox of redox-active building blocks has grown to include redox proteins, [2][3][4][5] inorganic complexes, [6,7] nanocrystals, [8] and several types of redox polyelectrolytes. [2,[9][10][11][12][13][14] Electrochemically active polyelectrolyte multilayers [15] have received widespread interest due to their potential applications in sensing, [2,4,9,10] electrochromic devices, [7][8][9]11] and as platforms for fundamental studies of redox proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction has been commonly used for amperometric detection of nitrate [6,15,16]. However, as also evident from Equation 1, there is a change in the H þ concentration as the nitrate is reduced to nitrite at the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…So to overcome some of the drawbacks of using NADH as a cofactor for fabrication of potentiometric nitrate biosensor and to possibly improve sensitivity, selectivity and stability of the biosensor, the use of redox mediator may also be considered. Several redox mediators have been used previously for the fabrication of amperometric biosensors [6,15,16], but to our knowledge none has ever been used for fabrication of potentiometric nitrate biosensors. Another potential benefit in considering the replacement of NADH with a redox mediator is economic.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to fabricate modified electrodes based on viologen films [9] and by cation-anion interaction of polyviologens with a negatively charged electrode surface. [10] Electropolymerization is another possibility to fabricate such interfaces and, as electropolymerization proceeds only at electrode surfaces, it is a particularly suitable method for the modification of area-defined electrodes. Electrochemically induced electrode modification involves electrochemically assisted adsorption of a polyviologen [11] or cross-linking a polymer with viologen oligomers.…”
Section: Introductionmentioning
confidence: 99%